تحديد مسؤولية القتل بواسطة الأسلحة المستقلة ذاتية التشغيل في الفقه الإسلامي: دراسة تأصيلية تحليلية: DETERMINING THE LIABILITY FOR KILLING BY AUTONOMOUS WEAPONS IN ISLAMIC JURISPRUDENCE: AN ANALYTICAL FOUNDATIONAL STUDY - Israr Khan; Hafiz Abdul Rehman (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
he technological advancements in our modern world present numerous jurisprudential challenges that necessitate deep contemplation and foundational studies to understand the Sharīʿah’s stance on them. Killing by autonomous weapons falls within this framework, prompting an exploration of the foundational aspect of the ruling on killing and determining accountability. These weapons perform all killing actions without human intervention, raising questions about the jurisprudential foundation of this killing. This paper aims to explore its foundational aspect and subsequently identifies its responsibility. It raises questions: Will the owner of such weapons bear responsibility as their possessor, or will it be the manufacturer, given that all software has been integrated into these weapons regarding the victim’s killing? Does the responsibility lie with both, as equals in the killing process, where the manufacturer embeds information about the victim, and the buyer spends money to purchase these weapons for killing? This proposed research aims to explore the jurisprudential rules related to determining responsibility, requiring a foundational jurisprudential analysis of the concept of the ruling and responsibility for killing in Islamic jurisprudence. The proposed methodology for the research includes examining Islamic legal and jurisprudential sources. Through this study, it is expected that jurisprudential discourse will contribute to understanding the determining accountability for killing using autonomous weapons.